Security as a new dimension in embedded system design - Kocher, Paul; Lee, Ruby; McGraw, Gary; Raghunathan, Anand (2004 41st Conference Design Automation, 2004)
The growing number of instances of breaches in information security in the last few years has created a compelling case for efforts towards secure electronic systems. Embedded systems, which will be ubiquitously used to capture, store, manipulate, and access data of a sensitive nature, pose several unique and interesting security challenges. Security has been the subject of intensive research in the areas of cryptography, computing, and networking. However, despite these efforts, security is often mis-construed by designers as the hardware or software implementation of specific cryptographic algorithms and security protocols. In reality, it is an entirely new metric that designers should consider throughout the design process, along with other metrics such as cost, performance, and power..This paper is intended to introduce embedded system designers and design tool developers to the challenges involved in designing secure embedded systems. We attempt to provide a unified and holistic view of embedded system security by first analyzing the typical functional security requirements for embedded systems from an end-user perspective. We then identify the implied challenges for embedded system architects, as well as hardware and software designers (e.g., tamper-resistant embedded system design, processing requirements for security, impact of security on battery life for battery-powered systems, etc.). We also survey solution techniques to address these challenges, drawing from both current practice and emerging research, and identify open research problems that will require innovations in embedded system architecture and design methodologies.